2022
DOI: 10.1177/15579883221107729
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Association Between Family Support and High-Risk Sexual Behavior of Elderly Men in Rural China

Abstract: Our study aimed to understand the relationship between the status of high-risk sexual behaviors of male ≥50 years old (elderly men) and their family support in a rural county-level city in Chengdu. Multi-stage sampling was used to select rural elderly men from six towns to conduct an interview questionnaire survey. Ordinal logistic regression was used to analyze the relationship between high-risk sexual behavior and family factors. A total of 790 samples were included, and the prevalence of high-risk sexual be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…33 34 Older men get little support from intimate social network, even from family members. 45 In this study, 52.70% of cases' intimate social network and sexual network were complete non-overlap, which means they did not receive social support from their sexual networks within the past 3 years. They are not close to their sexual partner, sexual behaviours are mainly commercial heterosexual behaviour (94.59%).…”
Section: Discussionmentioning
confidence: 66%
“…33 34 Older men get little support from intimate social network, even from family members. 45 In this study, 52.70% of cases' intimate social network and sexual network were complete non-overlap, which means they did not receive social support from their sexual networks within the past 3 years. They are not close to their sexual partner, sexual behaviours are mainly commercial heterosexual behaviour (94.59%).…”
Section: Discussionmentioning
confidence: 66%
“…Magnusson et al (2019) also reported that young men and women's self‐control behaviors are significantly effective in high‐risk sexual behaviors 72 . Li et al (2022) examined the role of family in controlling sexual behaviors among older Chinese men and showed that family factors that were influenced by loneliness, satisfaction with life, financial support, and family responsibilities affect the control of high‐risk sexual behaviors 73 . Therefore, the family members' management of the patients' sexual behavior control will play an important role in reducing their high‐risk sexual behaviors.…”
Section: Discussionmentioning
confidence: 99%